Development of Real-Time IoT-based Water Quality Monitoring System - SIEW ZHEN, LAU (IRC, 2019)
Water quality has to be sampled, tested and monitored regularly as water is one of human’s most essential daily needs. Safe and clean water is essential for keeping the human society and civilization function properly, thus the water quality monitoring system can be used to make sure and determine whether the water taken from the sample source is safe to be consumed or used in our daily life. Malaysia is a country which is blessed with numerous water sources, especially fresh water source which shapes Malaysia to become a country which depends and utilises heavily on water for daily operations. However, there is more than one-third of rivers in Malaysia are labelled as “slightly polluted”. Current water quality monitoring system is time consuming and inefficient. For this research, a device which can monitor the water quality of water sources will be designed and implemented. This device is aimed to provide accurate and reliable results by utilizing not only one but multiple sensors where each of them is tasked to measure different elements of the water. This whole system will be IoT (Internet of Things) based to achieve real time data transfer. Real time monitoring for water quality is important in ensuring the water pollution level can be detected as soon as possible.